3-(1H-Benzo[d]imidazol-6-yl)-5-(4-fluorophenyl)-1, 2, 4-oxadiazole (DDO7232), a Novel Potent Nrf2/ARE Inducer, Ameliorates DSS-Induced Murine Colitis and Protects NCM460 Cells against Oxidative Stress via ERK1/2 Phosphorylation. (20th May 2018) - Xu, Li-Li; Liu, Tian; Wang, Lei; Li, Li; Wu, Yu-Feng; Li, Cui-Cui; Di, Bin; You, Qi-Dong; Jiang, Zheng-Yu
Abstract : Ulcerative colitis (UC) is a common inflammatory bowel disease that can destroy the integrity of the colon and increase the risk of colorectal cancer. Oxidative stress is one of the critical pathogenic factors for UC, further impairing the entire affected colon. The Nrf2-ARE signaling pathway plays an important role in counteracting oxidative and electrophilic stress. Activation of the Nrf2-ARE pathway provides an indispensable defense mechanism for the treatment of UC. In this study, we identified a novel effective Nrf2 activator, DDO7232, which showed protective effects on NCM460 cells and therapeutic effects on DSS-induced colitis in mice. Mechanistic studies indicated that the Nrf2-ARE-inducing activity of DDO7232 was based on the activation of the ERK1/2 phosphorylation. The phosphorylation of Nrf2 Ser40 by p-ERK triggered the transport of Nrf2 into the nucleus and drove the expression of Nrf2-dependent antioxidant proteins. These results not only revealed the antioxidant mechanisms of DDO7232 but also provided an effective therapeutic option for the treatment of UC.